Not only Profit: How Strategic Management Works in Oil and Gas Industry (O&G) to Achieving Sustainability? - Mansurni Abadi; Nia Nur Pratiwi; Suniadewi Ayu Putu (Proceeding International Conference Restructuring and Transforming Law, 2024)
The importance of sustainable development goal (SDG) in the oil and gas (O&G) industry is undeniable, and it needs to be understood by businesses, firms, and the government to be fully developed and implemented. This study proposes the possible solutions in making growth towards sustainable energy production. A systematic review of literature was conducted to identify and synthesize the existing knowledge on the topic. This study examines the implementation of marketing performance measurement (MPM), green governance, and project development as part of strategic management. The findings indicate that the MPM, green governance, project development and strategic management will positively impact the achievement of the sustainable development goals, applicable to the O&G firms and political leaders. A cohort-specific prioritization of the tools is provided within strategic management growth in the industry.